A PESTLE analysis of the trucking industry: key insights and implications - Pamela Torres-Nunez; David Güemes-Castorena; Angel Contreras-Cruz; Armando Elizondo-Noriega (Cogent Business & Management, 2024)
Trucks are essential for transporting goods in today's economy, and heavy truck technology is advancing rapidly. New advancements include electric trucks, internet of things applications, and advanced safety features. However, there are challenges with adopting emerging technologies, such as autonomous trucks and artificial intelligence, as well as issues like driver shortage, safety, fuel costs, and contamination. Despite advancements, comprehensive research is still needed to address all factors impacting the industry. In this study, we conducted a systematic analysis using the PRISMA methodology to identify and analyze the factors impacting the trucking industry to better understand future driving forces. We searched the Web of Science and Scopus databases for January 2018 to July 2024 records. We analyzed 66 out of 108 selected records using the PESTLE methodology, which examines Political, Economic, Social, Technological, Legal, and Environmental factors. Our results show that 87% of the investigations focused on technological, social, and environmental factors, while 13% focused on other topics. Our findings show the significant impact of technology on the industry. Electric trucks introduce various implications, including fully autonomous trucks, the need for modern infrastructure, the displacement of drivers, and the demand for more advanced skills to operate increasingly high-tech trucks. The introduction of policies related to emission reduction, taxes, and subsidies for clean energy faces resistance from drivers, managers, and owners. Other key findings included the barriers to adopting alternative fuels, such as the need for charging stations and distribution networks and the need for implementing policies that support alternative energy sources.
Keywords: 650; PESTLE analysis; transportation; trucks; trucking industry; systematic analysis